Shareholder Protection and Agency Costs: An Experimental Analysis - LaRiviere, Jacob; McMahon, Matthew; Neilson, William (Management Science, 2018)
Two competing principal–agent models explain why firms pay dividends. The substitute model proposes that corporate insiders pay dividends to signal and build trust with outside shareholders who lack legal protection. The outcome model, in contrast, surmises that when shareholders have legal protection, they demand dividends from insiders to prevent them from expropriating corporate funds. Either way, dividends represent an agency cost paid to align the interests of shareholders and insiders. Expropriations by insiders and reduced investment by shareholders are also agency costs, but they are difficult to identify with archival data. Using a laboratory experiment, we identify the impact of strengthened shareholder protection on all three types of agency costs. Dividend payout ratios are five times larger with stronger investor protection, insider expropriation ratios are twice as high, and outsider investment falls by 45%. Thus, we find evidence that strengthening shareholder protection introduces previously unidentified agency costs into the insider–investor relationship. Data and the online appendix are available at https://doi.org/10.1287/mnsc.2017.2770 . This paper was accepted by Uri Gneezy, behavioral economics.